2022
DOI: 10.3758/s13421-022-01284-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequential versus simultaneous presentation of memoranda in verbal working memory: (How) does it matter?

Abstract: To-be-memorized information in verbal working memory (WM) can be presented sequentially, like in oral language, and simultaneously, like in written language. Few studies have addressed the importance and implications for verbal WM processing of these two presentation modes. While sequential presentation may favor discrete, temporal encoding processes, simultaneous presentation may favor spatial encoding processes. We compared immediate serial recall tasks for sequential versus simultaneous word list presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…presentation, but hearing nonsigners did not show this decrease in errors when moving from one presentation to the other. As predicted by prior studies of simultaneous presentation (Ordonez Magro et al, 2022), the simultaneous presentation format yielded lower omission errors than did sequential presentation, but only for the Deaf signers. In other words, Deaf signers were uniquely able to capitalize on the simultaneous presentation to reduce omission errors when compared with the sequential presentation.…”
Section: Item-level Correct Responses and Errorssupporting
confidence: 76%
See 3 more Smart Citations
“…presentation, but hearing nonsigners did not show this decrease in errors when moving from one presentation to the other. As predicted by prior studies of simultaneous presentation (Ordonez Magro et al, 2022), the simultaneous presentation format yielded lower omission errors than did sequential presentation, but only for the Deaf signers. In other words, Deaf signers were uniquely able to capitalize on the simultaneous presentation to reduce omission errors when compared with the sequential presentation.…”
Section: Item-level Correct Responses and Errorssupporting
confidence: 76%
“…Third, we predict this main effect will be qualified by a Group × Recall Direction interaction, wherein the Deaf group would exhibit a smaller forward-backward recall span difference than the hearing group (Bavelier et al, 2008, Experiment 3). Fourth, we predict a main effect of presentation format, wherein both groups will experience greater spans with simultaneous presentation than with sequential presentation (Ordonez Magro et al, 2022). Moreover, we hoped to extend the work of Hirshorn et al (2012) who found that Deaf signers could take advantage of visuospatial sequential location information to augment memory for verbal labels.…”
Section: Hypothesesmentioning
confidence: 72%
See 2 more Smart Citations
“…It should also be noted that one recent study (Harrison et al, 2020) of written language production (written and typed word production) also argues in favor of some flexibility in the representation of segment order. Hence, the flexible order-encoding of linguistic units (e.g., phonemes and letters for spoken and written word comprehension and production) would appear to be modality-independent and could thus constitute a general mechanism in language processing, which could also be applicable to a wide range of cognitive processes requiring the processing of order information (see Logan, 2021; Ordonez Magro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%